62.1k views
1 vote
I have 3 different ones now. I apologize for the relentless questions.

I have 3 different ones now. I apologize for the relentless questions.-example-1

1 Answer

4 votes

Answer:


(1)/(4x)

Explanation:

The negative exponential can be represented with the help of fractions. By this way, we also make the negative exponential disappear. For example, we can write:


a^(-1) = (1)/(a)

The explanation is this:

Since
a^(0)=1, (1)/(a)=(a^(0) )/(a^(1) ) = a^(0-1) =a^(-1)

According to this definition, we can simplify our problem in the following way:


(4x)^(-1) = (1)/((4x)^(1) ) = (1)/(4x)

User Lanorkin
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.